Efusi Pleura Et Causa Tb Paru - dewi murni manihuruk; Serli Alnamira Lorenza (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Pleural effusion is a condition where there is a buildup of fluid exceeding normal in thepleural cavum between the parietal and visceral pleura in the form of transudate or exudate fluid.Several diseases can cause pleural effusion, including tuberculosis lung infection, blunt andpenetrating trauma, and congestive heart failure. Case: Mrs. N, a 61-year-old woman, came withcomplaints of shortness of breath since 7 days accompanied by fever, bloody cough, weight lossdue to decreased appetite, the patient had a history of hypertension. Conclusion: The patient hasbeen diagnosed based on anamnesis, physical examination and supporting examination. And thepatient has been treated with medical measures and pharmacological therapy in accordance withthe patient's condition.